2017
DOI: 10.1021/acs.organomet.7b00015
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Polymerization by Dinuclear Zirconium Catalysts Based on Rigid Teraryl Frameworks: Effects on Tacticity and Copolymerization Behavior

Abstract: Toward gaining insight into the behavior of bimetallic catalysts for olefin polymerization, a series of structurally related binuclear zirconium catalysts with bisamine bisphenolate and pyridine bisphenolate ligands connected by rigid teraryl units were synthesized. Anthracene-9,10-diyl and 2,3,5,6-tetramethylbenzene-1,4-diyl were employed as linkers. Bulky Si i Pr 3 and SiPh 3 substituents were used in the position ortho to the phenolate oxygen. Pseudo-C s and C 2 symmetric isomers are observed for the binucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Precatalysts 1 – 4 (Figure ) were prepared as previously described . These precatalysts were selected for the current study due to the relative ease by which the C 2 isomers of the bimetallic catalysts could be isolated on moderate scales.…”
Section: Results and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Precatalysts 1 – 4 (Figure ) were prepared as previously described . These precatalysts were selected for the current study due to the relative ease by which the C 2 isomers of the bimetallic catalysts could be isolated on moderate scales.…”
Section: Results and Discussionsupporting
confidence: 75%
“…Our previously reported dizirconium olefin polymerization catalysts represent suitable candidates for studies of early transition metals, addressing the differences in performance of bimetallic and monometallic precatalysts in polar comonomer copolymerization. , We have employed bimetallic versions of the zirconium bisamine bisphenolate catalysts based on a rigid teraryl framework ( G ) and showed that isotactically enriched poly­(α-olefins) are generated via a site epimerization mechanism . The dizirconium catalysts show enhanced activity relative to monozirconium controls, and a subsequent study demonstrated that such catalysts could also be employed for ethylene-α-olefin copolymerization . These results provide a substantial basis for comparison to probe the effect of the catalyst nuclearity on the copolymerization of ethylene and comonomers bearing functional groups such as alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Sampson et al . also reported broader MWDs with multi‐modal distributions for all polymers obtained using bimetallic zirconium catalysts compared to those obtained by monometallic catalysts . It also can be suggested that the polymerization kinetics of bi‐ and multinuclear catalysts is complex and different from that of mononuclear catalysts.…”
Section: Resultsmentioning
confidence: 84%
“…This observation may for two reasons: first, the electronic effect of acenaphthene group on the backbone that leads to fewer chain transfer reactions; and second, the stronger synergistic effect resulted from chain walking . Also, the poly (1‐hexene) obtained in the presence of binuclear catalysts showed less chain branching than that obtained in the presence of mononuclear catalyst (MN).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation